2012
DOI: 10.1037/a0028282
|View full text |Cite
|
Sign up to set email alerts
|

A computer-based intervention to reduce internalized heterosexism in men.

Abstract: Internalized heterosexism (IH) is a strong predictor of the psychological well-being of lesbian, gay, bisexual (LGB), or other same-sex attracted individuals. To respond to the call for interventions to address IH, the current study developed and tested an online intervention to reduce IH among gay, bisexual, and other same-sex attracted men. A total of 367 self-identified same-sex attracted adult males were recruited through various nationwide LGB-related sources and were assigned by birth month to either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 35 publications
1
97
0
3
Order By: Relevance
“…This investigator-adapted scale first used five items from the Homosexual Attitudes Inventory (Nungesser, 1983), which were adapted to be more interpretable for a youth population. This is a measure frequently used to assess IH (Grey et al, 2013) and this scale has been highly correlated with other measures of IH, including one that shows post-intervention decreases in IH (Lin & Istael, 2012). This scale included items such as, “Sometimes I wish I were not gay” and “Sometimes I feel ashamed of my sexual orientation.” Next, the investigative team added 17 items to the scale in order to capture a broader conceptualization of IH, including items that tapped into experiences of shame, self-blame, normative masculinity and desire to change sexual orientation (Ramirez-Valles, Kuhns, Campbell, & Diaz, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This investigator-adapted scale first used five items from the Homosexual Attitudes Inventory (Nungesser, 1983), which were adapted to be more interpretable for a youth population. This is a measure frequently used to assess IH (Grey et al, 2013) and this scale has been highly correlated with other measures of IH, including one that shows post-intervention decreases in IH (Lin & Istael, 2012). This scale included items such as, “Sometimes I wish I were not gay” and “Sometimes I feel ashamed of my sexual orientation.” Next, the investigative team added 17 items to the scale in order to capture a broader conceptualization of IH, including items that tapped into experiences of shame, self-blame, normative masculinity and desire to change sexual orientation (Ramirez-Valles, Kuhns, Campbell, & Diaz, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It would be valuable, then, for future work to examine potential ways to help connect this population to counseling. One example of this can be found in Lin and Israel's (2012) report on a computer-based intervention that was designed to treat IH in men. Their work revealed that the online intervention was successful in reducing levels of some dimensions of IH in their sample, suggesting that technology may serve as one mechanism for linking with hard-to-access populations.…”
Section: Current Limitations and Future Directionsmentioning
confidence: 96%
“…Therefore, to treat gay and bisexual men’s psychosocial syndemics, standard cognitive restructuring approaches can be adapted to specifically reduce minority stress-fueled cognitive biases. This adapted cognitive restructuring approach could increase gay and bisexual men’s awareness of the specific ways that minority stress can become internalized and the unhealthy impact this internalization can have, while presenting contradictory evidence highlighting gay and bisexual men’s unique strengths (e.g., Lin & Israel, 2012). While the development of cognitive biases, such as fears of gay-related rejection, may have been adaptive across some gay and bisexual men’s early development because it kept them safe from harm, such biases may be presently maladaptive especially in safer contexts (Pachankis & Goldfried, 2006) and might impair healthy relationships both with heterosexuals (e.g., Pachankis et al, 2008) and other gay and bisexual men (e.g., Frost & Meyer, 2009).…”
Section: Treatment Principles Of Transdiagnostic Minority Stress Syndmentioning
confidence: 99%